Selling lowbrow art and cultural goods in times of pandemic: The case of a provincial art market. Issue 3 (August 2022) - Radermecker, Anne-Sophie
Abstract: This article examines the impact of the coronavirus pandemic on a provincial art market to shed light on how gallerists, auctioneers, and antique dealers have coped with this exogenous event. Provincial intermediaries, active in the lower ends of the art market, are characterized by economic properties that differ from those of the upper-end markets. Their location at the periphery of metropolitan centers, combined with the characteristics of supply and demand, are likely to affect their ability to face a global crisis. Based on 15 semi-structured interviews with provincial intermediaries, this research reveals the unexpected performance of local auction houses and antique dealers active in the secondary art market. We attribute this performance to the use value of lowbrow cultural goods, the willingness of local auction houses to embrace the benefits of online two-sided markets, and their ability to offset a pent-up demand, especially among Generation Y. Recommendations to prompt provincial art market players to sustain the positive externalities of the crisis in the long run are provided.